The Ideologizing of the Historical Event in the Novel “Kitab El Amir” by Wasini Al-Araj - سفاري , جمال (Milev Journal of Research and Studies, 2024)
Many critics have read the Arabic historical novel and focused on the relationship between the narrative and historical sides of the novel and the extent of their interaction. These critics agreed on distinguishing between the real and imaginary dimensions in this novel because of its transgression of the realistic dimension. In this paper, we try to identify the implicit ideological pattern that was included in this transgression (bypassing the real dimension of the novel to account for the imaginary dimension in it) and directed it to the ideologicalization of the historical event in the novel “Kitab el Amir” by novelist Wasini Al-Araj. This led to breaching the horizon of waiting for the reader who had a preconceived picture about the events in Algeria at the time of Emir Abdelkader.